2002
DOI: 10.1159/000066149
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Teachers’ Speech during a Working Day with and without Electric Sound Amplification

Abstract: An increase in fundamental frequency (F₀) and in sound pressure level (SPL) has been reported both after vocal loading tests and after a teacher’s working day. This increase has been found to be greater among teachers with fewer voice complaints. The present study investigated speech changes during a teacher’s working day (a) in ordinary conditions and (b) when using electric sound amplification while teaching. Five Icelandic teachers (mean age 51 years) volunteered as subjects. Classroom speech was recorded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 13 publications
3
50
0
1
Order By: Relevance
“…An increase in fundamental frequency has been interpreted as a healthy reaction to voice load in other studies. Laukkanen et al 15 , and Jonsdottír et al 16 showed the F0-rise rise to be more evident after voice amplification, unburdening the voice. Rantala and Vilkman 9 found F0 changes to be significant in a group of teachers with few complaints of voice problems but not in the compared group with many complaints.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An increase in fundamental frequency has been interpreted as a healthy reaction to voice load in other studies. Laukkanen et al 15 , and Jonsdottír et al 16 showed the F0-rise rise to be more evident after voice amplification, unburdening the voice. Rantala and Vilkman 9 found F0 changes to be significant in a group of teachers with few complaints of voice problems but not in the compared group with many complaints.…”
Section: Discussionmentioning
confidence: 97%
“…Laukkanen et al 15 described the rise of F0 as a result of an increase in muscular activity, most likely an adaptation to vocal loading during a day at work. In addition, they described that the voice changes during vocal loading include an increase of the SPL and a decrease of jitter and shimmer.. Also Jónsdóttir et al 16 suggests that an F0 increase is a healthy reaction to voice load that promotes effective voice function. However, there seems to be a deviant pattern of the increase of F0 in individuals with voice problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, as a general rule, it should be noted that females experience a higher raw cycle dose due to their higher natural F 0 . 1,[4][5] It is possible that female vocal fold tissue structure is somewhat adapted for these higher vibration doses. 2 Anecdotally, some singers report returning to their subjective baseline quickly from episodes of vocal fatigue while others do not.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue in the pathogenesis of occupational dysphonia in this professional group is the use of incorrect techniques of voice production causing improper compensation of heavy vocal loading [9]. Furthermore, classroom environment with improper acoustic and reverberation parameters may increase vocal effort of the speaker [10,11]. Also, a poor microclimate comprising dust or even organic pollution, poor humidity, and exposure to fluctuations of temperature may affect the condition of the larynx mucosa in professional speakers and thus enhance voice problems [12,13].…”
Section: Etiopathology Of Occupational Voice Disordersmentioning
confidence: 99%